Kurikukulum Merdeka: Problematik Guru dalam Implementasi Teknologi Informasi pada Proses Pembelajaran - Aulia, Aan Fitri; Asbari, Masduki; Wulandari, Siti Ayu (AGUSPATI RESEARCH INSTITUTA, 2024)
The use of technology in education has become a major focus to improve the quality of learning in Indonesia. However, many teachers face a number of problematic issues in adopting and utilizing Technology in the learning system. The purpose of this study is to identify and analyze the challenges faced by teachers in Implementation Technology Information in the learning process. This study report uses a descriptive qualitative method by doing simak catat because the data system is obtained by listening to oral narratives from the youtube channel news one entitled